2013
DOI: 10.1590/s0102-09352013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic changes in propofol-anesthetized dogs with or without tramadol administration

Abstract: Drugs commonly used in anesthesia practice may significantly alter the oxidative state of blood cells. This mechanism could contribute to the immune suppression that occurs transiently in the early postoperative period. Thus, we assessed the effects of continuous rate infusion (CRI) of propofol associated or not with tramadol on hematologic parameters in dogs. Eight adult mongrel dogs were anesthetized on 2 occasions, 15 d apart. Two groups were formed: control group (CG) and tramadol group (GT). Propofol was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
3
8
0
6
Order By: Relevance
“…These observations were in agreement with the results of the previous studies that reported the oxidative stress induced by the tramadol in brain. [31][32][33][34] The tramadol not only induced oxidative stress in brain but also was associated with significant decrease in brain non-enzymatic antioxidant, intracellular reduced glutathione level and enzymatic antioxidant and glutathione peroxidase activity. 35 Moreover, it has been reported that oxidative modifications resulted in a loss of function and lowering of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were in agreement with the results of the previous studies that reported the oxidative stress induced by the tramadol in brain. [31][32][33][34] The tramadol not only induced oxidative stress in brain but also was associated with significant decrease in brain non-enzymatic antioxidant, intracellular reduced glutathione level and enzymatic antioxidant and glutathione peroxidase activity. 35 Moreover, it has been reported that oxidative modifications resulted in a loss of function and lowering of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…The observed leucopoenia was at the expense of lymphocytes as recorded by Costa et al (2013). This alteration was in unison with elevation in cortisol values starting right at the 30 th min but most pronounced at 140 th min.…”
Section: Discussionmentioning
confidence: 61%
“…in the same group; p < 0.05;  p < 0.01 -statistically significant differences compared to the control group for the respective period; p<0.05 -statistically significant differences compared to the epidural group for the respective period; *p < 0.05; ** p < 0.01; ***p<0.001 -statistically significant differences compared to the initial period (0 min.) in the same group; p < 0.05 -statistically significant differences compared to the control group for the respective period; p<0.05 -statistically significant differences compared to the epidural group for the respective period (Costa et al, 2013) connected with anaesthesia. Most of the studies on the effects of anaesthesia on the immune function were performed in vitro, or in patients submitted to some kind of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Visto que a PaO 2 e a SaO 2 permaneceram estáveis no GMF (193mm/Hg e 98,1%) e no GCM (195 mm/Hg e 98,3%), acredita-se que a redução da CaO 2 ocorreu devido à leve redução da hemoglobina (tHb) arterial de 10% no GMF e de 13% no GCM, permanecendo as médias em 12±1,2g/dL no GMF e em 11,9±1,3g/dL no GCM. Costa et al (2013) citam leve diminuição gradativa da tHb durante infusão de propofol (0,7mg/kg/min), possivelmente devido à redistribuição de eritrócitos para locais não esplênicos. Outro fator que pode ter auxiliado a diminuição da tHb é a hemodiluição, visto que a lavagem dos cateteres a cada avaliação, a infusão dos tratamentos e o fornecimento de nutrição parenteral podem ter influenciado esses valores.…”
Section: Resultsunclassified
“…Ethier et al (2008) citam uma diminuição de 15% na DO 2 , com protocolo de propofol, diazepam/midazolam e fentanil, porém sem alteração da perfusão tecidual. A anestesia normalmente diminui a DO 2 (Haskins, 2006), possivelmente pela ação dos fármacos na redução do IC ou, ainda, pela redistribuição de eritrócitos e consequente diminuição da hemoglobina circulante e da CaO 2 (Costa et al, 2013). Porém, Haskins (2006) O pH arterial (7,32±0,06 no GMF e 7,31±0,03 no GCM) e o venoso misto (7,29±0,07 no GMF e 7,26±0,06 no GCM) estavam levemente abaixo dos valores de referência no momento basal (Ha et al, 2013), devido aos maiores valores da PaCO 2 , de 47,9±6,6 no GMF e de 49,6±4,9mm/Hg no GCM nesse momento, possivelmente pela respiração espontânea sob anestesia geral inalatória, a qual pode promover depressão respiratória dose-dependente (Galloway et al, 2004).…”
Section: Resultsunclassified